The Position of Customary International Law in the Polish Legal System in the Light of Article 9 of the Constitution of 1997 - Wójtowicz, Krzysztof (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
In 1997, when the Constitution currently in force was adopted, the Polish constitution-maker made the legal system open to the provisions of international law – at least in part – for the first time in the post-war period. Article 9 of the Polish Constitution (1997) gives evidence to this openness. It states that “The Republic of Poland shall respect international law binding upon it”. An expression “international law” used here should be understood as a set of norms binding in relations between subjects of this law, first of all between states and international organizations. Special attention is paid to the respective position of customary law.
Keywords: prawo zwyczajowe; prawo polskie; Konstytucja